Worlds of childhood - Wozniak, Robert H.; Wozniak, Robert H.; Rourke, Mary T.; Haahr, Berit I. (New York, N.Y. : HarperCollins College Publishers, 1993)
"[The book] has been specifically designed to bring the work of developmental psychologists together with that of historians of childhood, psychological anthropologists, sociologists, psycholinguists, and experts in other fields, to examine the diversity of children's development in the complex, changing social contexts in which it occurs. In the [book's] chapters ... we will be studying children as they change within these developing contexts. Through this study we will be led to a deeper understanding of the many forces that bring about change--change in individuals, in families, in societies, and in humankind"--Introd.
Development and diversity -- Ecology of development -- Heredity and environment: prenatal development; evolution, environment, and growth; nature and nurture interwoven -- Culture and context: culture, time, and place; changing families and systems of support -- Children and families: individual differences and developmental milestones; symbol formation and the acquisition of language; concepts and categories, meanings and memories; responsive caregiving; interactional styles and attachment; gender, self, and other; rivalry and interdependence in sibling relationships -- Schooling: daycare and the American "cult of motherhood"; mathematics achievement and the Asian advantage -- Peer relationships: friendship, gender, and morality; peer culture -- Culture, time, and place: adolescence, the prolonged transition; risk and resilence; child at work; death, divorce, and remarriage, the child's perspective.
Cover title: Worlds of childhood reader.
Includes bibliographical references.
Keywords: Child development; Child development -- Cross-cultural studies; Child psychology